Integrasi Islam dan Sains : Model Pembelajaran Integratif Al-Islam dan Sains di Universitas Muhammadiyah Mataram (UMMAT): Model Pembelajaran Integratif Al-Islam dan Sains di Universitas Muhammadiyah Mataram (UMMAT) - Anugrah Arifin; Dewi Urifah; Zaenudin Zaenudin (SUARGA: Studi Keberagamaan dan Keberagaman, 2025)
This research is focused on the formulation of an integrative learning model of Islam and Science at the Faculty of Agriculture (FAPERTA) of the University of Muhammadiyah Mataram (UMMAT). This research is class action research (PTK) with respondents consisting of 79 students in the second semester of the Agricultural Engineering, Agricultural Product Technology, and Regional Planning study program in 2021/2022. Observation, questionnaire, and triangulation became a data collection technique that was analyzed qualitatively in a descriptive manner, yielding findings. The development of integrative lectures on Islam and Science in Al-Islam II lectures (Fiqih Ibadah) is carried out by developing the theory of Bucalism (scientific ayatization) in the form of Scienceization of Fiqh Theories of Worship. The students' response to the application of the model development was: positive, 49-75 students (62% - 94.9%) had a positive attitude, 3-6 students (5%-7%) had a negative attitude, 24 students (30.4%) had a mediocre attitude, and there were no (0%) students who had a very negative attitude towards the use of the technique.